EVALUASI KARAKTERISTIK DAN OPTIMASI LAHAN BERDASARKAN KESESUAIAN LAHAN KEBUN BENIH SEMAI GMELINA (Gmelina arborea Roxb.) DAN TISUK (Hibiscus macrophyllus) Roxb. Ex Hornem) HUTAN KIARAPAYUNG, SUMEDANG, JAWA BARAT - Sunarya, Sopandi; Rumidatul, Alfi (Universitas Nusa Bangsa, 2024)
The degradation of forests in Indonesia has resulted in a decrease in the productivity of the land, necessitating the need for the restoration and expansion of forest planting. The primary issue with forest rehabilitation activities is that the characteristics of the growing area are typically marginal and deficient in nutrients. Furthermore, each plant possesses distinct attributes and appropriateness for its specific growing environment. Hence, in order to perform suitable site engineering, it is imperative to undertake land evaluation activities to ascertain the suitability of the land for cultivation and to identify any constraints on the land. The objective of this study is to determine the attributes of the habitat and the factors that restrict the growth of G. arborea and H. macrophyllus seedlings in the Kiarapayung forest. We conducted measurements of soil samples, rainfall, slope, and altitude. The rate analysis identified five suboptimal parameters in the G. arborea seedling seed garden land: slope, soil pH, C-organic, N, P, and K potent. Within the suboptimal category, the H. macrophyllus land is characterized by a single parameter, which is the slope. In order to attain the most favorable plant growth, it is imperative that we enhance the six factors that currently restrict growth on this research land. To enhance the inadequate preservation and accessibility of essential nutrients such as pH, C-organic, N, available P, and potential K, it is recommended to administer lime and fertilizer to the soil.